Dynamics of the electrospondilography indices of the individuals with back pain under the influencing of the physical rehabilitation program. Physical rehabilitation of the individuals with back pain - O. K. Nikanorov; V. V. Kormiltsev; I. O. Zharova; O. B. Lazareva; L. D. Kravchuk (Zaporozhye State Medical University, 2019)
Back pain (BP) is an important link in neurological pathology and one of the most common complaints in general medicine practice. The purpose of the research was: scientifically and strategically substantiate and develop a comprehensive physical rehabilitation program of persons with dorsalgia in the thoracic spine and to prove its effectiveness according to the data of the electrospondilography. Materials and methods. The study was conducted on the basis of the sports and rehabilitation club "Fifth Element" in Kyiv, 67 patients (25 men and 42 women) were taking part in our research, of the working-age with BP on the thoracic level. Results. Based on the results of previous studies, we have developed a complex physical rehabilitation program for patients with BP on the thoracic spine, which included various tools and forms of physical rehabilitation, elements of modern fitness techniques, soft tissue and connective tissue manipulative techniques, and a cognitive method -conductive therapy. Conclusion. The effectiveness of the developed program of patients with BP in the thoracic department was evaluated after the completion of the course - after 12 weeks. According to the data of ESG, the positive dynamics of indicators K1, K2, K3, К4 was observed in both the MG and CG. However, only in the MG of changes in K3 and K4 indicators were statistically significant.